FAKTOR PENENTU KEPUTUSAN PEMBELIAN BERAS DI KIOS REJO MAKMUR, SALATIGA - Laila Kusumaning Ayu; Lasmono Tri Sunaryanto (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2020)
Indonesia is the highest consumer of rice per capita in the world with the largest amount. The main factor driving high consumption is the large population. The high consumption of rice also affects the competition for rice sales. Increasingly high competition makes rice producers begin to learn about rice purchasing decisions. This study aims to analyze the factors that influence rice purchasing decisions in Rejo Makmur Kiosk, Salatiga. This research uses descriptive qualitative method with multiple linear regression analysis. Respondents obtained by accidental sampling method and data obtained using a questionnaire. The results showed that price (X1), product (x2), promotion (X3), and location (X4) factors simultaneously had a significant effect on rice purchasing decisions (Y) in Rejo Makmur Kiosk. Partially the factors that have a significant influence on consumer purchasing decisions are price, product and promotion factors, while location factors have no effect. The ability of the independent variable in explaining the purchase decision variable is 75.4%, while the remaining 24.6% is influenced by other variables outside this regression equation or unknown variables.